Prevalence of Hypertension in a selected Rural Area of Mymensingh - Hasan, AHM; Alam, Fakir Sameul; Hossain, Md Tufael; Begum, Maksuda; Dipu, Sultana Sobnam; Tahera, Sadiqa (Community Based Medical Journal, 2016)
This cross-sectional descriptive study was carried out from January 2015 to March 2016 in villages of 12 Bhavokhali union, Sadar upazila, Mymensingh. The study was done on 408 subjects who were selected purposively. Data were collected on a pre-designed questionnaire by direct interviewing the respondents. Data analysis was done using SPSS version 16. Prevalence of hypertension was 21.32%. Mean age was 39.22 years and standard deviation 14.81 years. Prevalence of hypertension was 46.30% among persons over 60 years of age, 37.11% among persons having family history of hypertension, 61.54% among persons having diabetes mellitus, 43.96% among persons having BMI more than or equal to 25, 29.41% among those having sedentary lifestyle, 22.14% among those having the habit of added salt intake, 33.75% among smokers and 25.95% among persons having the habit of smokeless tobacco intake. Though female had low prevalence of hypertension (18.77%), female working outside had higher prevalence 31.59%. Women of reproductive age group had lower prevalence of hypertension (15.56%) among whom oral contraceptive pill users had increased prevalence of hypertension 16.82%. Prevalence of hypertension found in this study was lower in comparison to global prevalence and results of other studies. CBMJ 2016 July: Vol. 05 No. 02 P: 14-20